Comparative study of MTA and other materials in retrofilling of pulpless dogs' teeth - Bernabé, Pedro Felício Estrada [UNESP]; Holland, Roberto [UNESP]; Morandi, Ricardo [UNESP]; Souza, Valdir de [UNESP]; Nery, Mauro Juvenal [UNESP]; Otoboni Filho, José Arlindo [UNESP]; Dezan Junior, Eloi [UNESP]; Gomes Filho, João Eduardo [UNESP] (FapUNIFESP (SciELO), 2005)
This in vivo study compared the effect of mineral trioxide aggregate (MTA), IRM, Super EBA and ZOE in a puttylike consistency, used as retrofilling materials, in the healing process of periapical tissue of pulpless dogs' teeth submitted to a conventional retrofilling technique. Twenty-four premolars obtained from three dogs were used. At the first intervention, the animals were anesthetized, coronal access was obtained and pulpectomy was done. Root canals were kept open to the oral environment for 180 days to induce the formation of apical lesions. After surgical removal of the lesions with curettes, 2 mm of the apical root was cut out perpendicular to the long axis of the teeth, and root-end cavities were shaped with a low-speed round bur. The bone cavities were irrigated and dried, and the root-end cavities were filled with MTA, IRM, Super EBA and ZOE in a puttylike consistency. The bone cavities were passively filled with blood and flaps were sutured. The coronal access openings were cleaned and double-sealed with ZOE and amalgam. After 180 days, the animals were killed by anesthetic overdose, maxilla and mandible were removed and the pieces were processed for histomorphologic analysis. Data were evaluated blindly on the basis of several histopathologic events and the scores obtained were analyzed statistically using the Kruskal Wallis test. No significant differences were observed among MTA, Super EBA and IRM (p>0.05). However, ZOE had a significantly more negative influence on the apical healing (p<0.05). In conclusion, MTA, Super EBA and IRM had similar histopathologic effects among each other and better performance than ZOE used in a puttylike consistency. Furthermore, only MTA stimulated hard tissue deposition in direct contact with the retrofilling material, even when it was inserted under critical conditions.
Keywords: Apical surgery; Mineral trioxide aggregate; Retrofilling; aluminum derivative; calcium derivative; dentin bonding agent; IRM cement; methacrylic acid methyl ester; mineral trioxide aggregate; oxide; root canal filling material; silicate; Super EBA; zinc oxide eugenol; animal; cementum; comparative study; curettage; dentin; dog; drug combination; endodontics; pathology; periodontium; single blind procedure; time; tooth periapical disease; tooth pulp disease; wound healing; Aluminum Compounds; Animals; Apicoectomy; Calcium Compounds; Curettage; Dental Cementum; Dentin; Dentin-Bonding Agents; Dogs; Drug Combinations; Methylmethacrylates; Oxides; Periapical Diseases; Periapical Tissue; Pulpectomy; Retrograde Obturation; Root Canal Filling Materials; Root Canal Preparation; Silicates; Single-Blind Method; Time Factors; Tooth, Nonvital; Wound Healing; Zinc Oxide-Eugenol Cement